Penerapan Metode Logika Fuzzy Mamdani Untuk Menentukan Jumlah Pendapatan Penjualan Produk Umpan Pancing - Binurilfatikhah, Barikna; Tri Hastono; Tyas Sulistyawati (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2024)
Anugerah Jaya Finishing Store 99 is one of the online stores that sells fishing bait. Fishing bait is a crucial factor in improving the efficiency of fish capture, and there are two types of fishing bait : artificial bait and natural bait. Income is the money generated from the sale of goods or services to costumers and is the most important aspect in determining the smooth operation of a business. To determine the amount of income in this study, one of the fuzzy logic methods, namely mamdani fuzzy logic, was used. Mamdani fuzzy logic was chosen because it is the method that is most similar to human logic.